2021
DOI: 10.1108/jeas-08-2020-0153
|View full text |Cite
|
Sign up to set email alerts
|

Examining investors' sentiments, behavioral biases and investment decisions during COVID-19 in the emerging stock market: a case of Pakistan stock market

Abstract: PurposeThis study investigates the impact of the COVID-19 pandemic on investors' sentiments, behavioral biases and investment decisions in the Pakistan Stock Exchange (PSX).Design/methodology/approachThe authors have assessed investors' behaviors and sentiments and the stock market overreaction during COVID-19 using a questionnaire and collected data from 401 investors trading in the PSX.FindingsResults of structural equation modeling revealed that the COVID-19 pandemic affected investors' behaviors, investmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 58 publications
1
29
0
1
Order By: Relevance
“…Shrotryia and Kalra (2021) examined the existence of overconfidence bias on emerging and frontier markets in the Covid-19 pandemic period and found evidence of overconfidence bias in the Covid-19 pandemic period. Similarly, Parveen et al (2021) revealed that the Covid-19 pandemic had an effect on the investor's behavior, investment decisions and trading volumes. Specifically, they reported that the biases, such as representative heuristic, anchoring, overconfidence bias and disposition effect, were observed to have a negative impact on investors' investment decisions at the Pakistan stock market during the Covid-19 pandemic period.…”
Section: Introductionmentioning
confidence: 99%
“…Shrotryia and Kalra (2021) examined the existence of overconfidence bias on emerging and frontier markets in the Covid-19 pandemic period and found evidence of overconfidence bias in the Covid-19 pandemic period. Similarly, Parveen et al (2021) revealed that the Covid-19 pandemic had an effect on the investor's behavior, investment decisions and trading volumes. Specifically, they reported that the biases, such as representative heuristic, anchoring, overconfidence bias and disposition effect, were observed to have a negative impact on investors' investment decisions at the Pakistan stock market during the Covid-19 pandemic period.…”
Section: Introductionmentioning
confidence: 99%
“…This means that they were scared of the pandemic circumstances, yet hopeful that new solutions will be unearthed for prevention and recovery. Moreover, emotions regarding economy have been very negative during the COVID-19 pandemic (64,65). The study in (64,65) show that at the beginning of the pandemic investors became very fearful and uncertain of the stock market trends and trading.…”
Section: Sentiment Classificationmentioning
confidence: 99%
“…Since the COVID-19 pandemic created dramatic uncertainty and panic among market participants worldwide (Ortmann et al, 2020;Talwar et al, 2021), few studies investigated the impact of such a pandemic on individual investor's behavioural factors. For example, Parveen et al (2021) investigated the impact of the COVID-19 pandemic on individual investors' behavioural biases, sentiments and investment decisions in the Pakistan Stock Exchange via using a questionnaire from 401 investors. Parveen et al (2021) found that the COVID-19 outbreak influenced the investor's investment decisions due to the fear and uncertainty caused by the COVID-19 pandemic.…”
Section: Covid-19 and Individual Equity Investor's Behaviourmentioning
confidence: 99%
“…For example, Parveen et al (2021) investigated the impact of the COVID-19 pandemic on individual investors' behavioural biases, sentiments and investment decisions in the Pakistan Stock Exchange via using a questionnaire from 401 investors. Parveen et al (2021) found that the COVID-19 outbreak influenced the investor's investment decisions due to the fear and uncertainty caused by the COVID-19 pandemic. They also found that the overconfidence bias and disposition effect negatively impacted investors' decisions.…”
Section: Covid-19 and Individual Equity Investor's Behaviourmentioning
confidence: 99%